Recent Progress in 3D Printing of Bioinspired Structures - Wang, Danfeng; Chen, Dongdong; Chen, Zeyu (Frontiers in Materials, 2020)
Over millions of years of evolution, the species in nature have gradually possessed some bio-structures. These structures have specific mechanical, hydrodynamic, optical, and electrical properties, which provide human the valuable enlightenments to design and fabricate high-performance components and devices. However, the traditional fabrication technologies cannot accurately reproduce or imitate the complicated and exquisite bioinspired structures, which restricts the development and application of biomimetic study. Due to the emergence and development of 3D printing technologies, more bioinspired structures can be designed and fabricated. Recent progress in 3D printing of structures inspired by the species in nature, such as springtails, filefish, abalone shell, conch shell, wheat awn, plant stem and wood, etc., are reviewed in this paper and the current challenge and future development for 3D printing of bioinspired structures are discussed.